Dzhangalina E.D., Zhumabayeva B.A., Aytasheva Z.G., Lebedeva L. P. Impact of lectins isolated from the bean callus culture on growing drought tolerance in plants: Al-Farabi Kazakh National University, Kazakhstan, Almaty (Eurasian Journal of Ecology, 2018)
Plant cell and tissue culture is a very prospective model to detect newsources of lectins, to study different ways of their regulation and to invent new biotechnological methods for isolation them from plants. It canhelp to use lectins as plant protectors in the future. It has been studiedthat lectins obtained from common beans calluses empower drought tolerance of legumes and grains and also positively influence on growingprocesses, water metabolism and prolin content. It has been shown thatlectins stimulate seeds to germinate, impact on plant height and biomass,water in tissues and rate of transpiration. This research can help to makenew biopreparations on the basis of common beans’ lectins to increaseproductivity of crops.Key words: common beans, lectins, water metabolism, drought tolerance, biopreparations